Therapeutic Innovation in DRE: Filling the Unmet Need with Emerging Modalities - Olesiński, Bruno; Niemiec, Bartosz; Piosik, Szymon; Dudziak, Natalia; Drozd, Zuzanna; Piasecki, Łukasz; Guzowicz, Zuzanna; Kamińska, Monika; Gągałka, Patrycja (Journal of Education, Health and Sport, 2025)
Background: Epilepsy - one of the most commonly known neurological disorders, is affecting over 50 million people worldwide. Despite advances in pharmacotherapy, about 30% of patients continue to experience uncontrolled seizures. This disease proved to be linked to cognitive decline, and higher mortality, confirming the need for effective therapeutic alternatives. Aim of the review: The aim of this paper is to provide a comprehensive review and analysis of current, scientifically proven treatments for drug-resistant epilepsy and drugs along with potential therapies under clinical trials. Material and methods. A systematic literature search was conducted using the PubMed, Google Scholar, Cochrane Library databases and the ClinicalTrials.gov website. Following removal of duplicates and relevance screening, 49 studies published from 2020 onwards with key studies included regardless of the publication date. Results: Newer-generation agents such as cenobamate, lacosamide, brivaracetam, and perampanel offer novel mechanisms and improved safety, while ganaxolone, padsevonil, and carisbamate are promising but yet in trials. Surgical interventions remain highly effective for selected patients, whereas minimally invasive techniques like MRI-guided laser ablation have broadened treatment options. Neuromodulatory approaches such as VNS, DBS, RNS should be utilized in inaccessible epileptogenic foci. Dietary interventions, particularly the ketogenic diet and its variants, show efficacy through different mechanisms. Experimental therapies, including gene-based interventions, interneuron transplantation, and immunomodulation, alongside biomarker-guided strategies, signal a shift toward individual medicine. Conclusions: DRE remains a major challenge, but therapeutic progress is evident. New treatments should be observed for adverse effects and for both adjunctive therapy and drug’s isolated effects.